Effect of distillation methods on the leaf essential oil of some Citrus cultivars - Sulzbach, Manuela; Silva, Magnólia Aparecida Silva da; Gonzatto, Mateus Pereira; Marques, Marcia Mayo Ortiz [UNESP]; Böettcher, Gerson Nestor; Silvestre, Wendel Paulo; Silva, Julio César Rodrigues Lopes [UNESP]; Pauletti, Gabriel Fernandes; Schwarz, Sergio Francisco (Taylor & Francis, 2021)
This study aimed to characterize the chemical composition of the leaf essential oil (EO) of mandarin and tangor trees obtained by steam distillation and hydrodistillation. Leaf samples were collected during the pruning period from seven citrus cultivars in a property located in Pareci Novo, Rio Grande do Sul state, South Brazil. The leaves underwent hydrodistillation and steam distillation, and the obtained EO was analyzed by GC-MS and GC-FID. In general, the Citrus deliciosa mandarins had higher EO yields than the ‘Ponkan’ and tangors in both methods. The Citrus deliciosa mandarin trees presented higher amounts of methyl N-methyl anthranilate and γ-terpinene. In the EO of ‘Ponkan’, ‘URSBRS Hada’ and ‘Murcott’, there was a predominance of linalool and terpinen-4-ol. The extraction method influenced the contents of the compounds mainly, while the genetic factors determined the variations in the composition of the essential oil of citrus leaves.
Keywords: c. reticulata; Citrus deliciosa; linalool; methyl n-methyl anthranilate; petitgrain; yield